Global, regional, and national burden of meningitis, 1990-2016: a systematic analysis for the Global Burden of Disease Study 2016 - Zunt, Joseph Raymond; Bärnighausen, Till (The lancet, 2018)
Acute meningitis has a high case-fatality rate and survivors can have severe lifelong disability. We aimed to provide a comprehensive assessment of the levels and trends of global meningitis burden that could help to guide introduction, continuation, and ongoing development of vaccines and treatment programmes.
GBD 2016 Meningitis Collaborators: Joseph Raymond Zunt, Nicholas J Kassebaum, Natacha Blake, Linda Glennie, Claire Wright, Emma Nichols, Foad Abd-Allah, Jemal Abdela, Ahmed Abdelalim, Abdu A Adamu, Mina G. Adib, Alireza Ahmadi, Muktar Beshir Ahmed, Amani Nidhal Aichour, Ibtihel Aichour, Miloud Taki Eddine Aichour, Nadia Akseer, Rajaa M Al-Raddadi, Fares Alahdab, Kefyalew Addis Alene, Syed Mohamed Aljunid, Mohammad A AlMazroa, Khalid Altirkawi, Nelson Alvis-Guzman, Megbaru Debalkie Animut, Mina Anjomshoa, Mustafa Geleto Ansha, Rana Jawad Asghar, Euripide F G A Avokpaho, Ashish Awasthi, Hamid Badali, Aleksandra Barac, Till Winfried Bärnighausen, Quique Bassat, Neeraj Bedi, Abate Bekele Belachew, Krittika Bhattacharyya, Zulfiqar A Bhutta, Ali Bijani, Zahid A Butt, Félix Carvalho, Carlos A Castañeda-Orjuela, Abdulaal Chitheer, Jee-Young J Choi, Devasahayam J Christopher, Anh Kim Dang, Ahmad Daryani, Gebre Teklemariam Demoz, Shirin Djalalinia, Huyen Phuc Do, Manisha Dubey, Eleonora Dubljanin, Eyasu Ejeta Duken, Maysaa El Sayed Zaki, Iqbal RF Elyazar, Hamed Fakhim, Eduarda Fernandes, Florian Fischer, Takeshi Fukumoto, Morsaleh Ganji, Abadi Kahsu Gebre, Afewerki Gebremeskel, Bradford D Gessner, Sameer Vali Gopalani, Yuming Guo, Rahul Gupta, Gessessew Bugssa Hailu, Arvin Haj-Mirzaian, Samer Hamidi, Simon I. Hay, Andualem Henok, Seyed Sina Naghibi Irvani, Ravi Prakash Jha, Mikk Jürisson, Amaha Kahsay, Manoochehr Karami, André Karch, Amir Kasaeian, Getachew Mullu Kassa, Tesfaye Dessale Dessale Kassa, Adane Teshome Kefale, Yousef Saleh Khader, Ibrahim A. Khalil, Ejaz Ahmad Khan, Young-Ho Khang, Jagdish Khubchandani, Ruth W Kimokoti, Adnan Kisa, Faris Hasan Lami, Miriam Levi, Shanshan Li, Clement T. Loy, Marek Majdan, Azeem Majeed, Lorenzo Giovanni Mantovani, Francisco Rogerlândio Martins-Melo, Colm Mcalinden, Varshil Mehta, Addisu Melese, Ziad A Memish, Desalegn Tadese Mengistu, Getnet Mengistu, Tomislav Mestrovic, Haftay Berhane Mezgebe, Bartosz Miazgowski, Branko Milosevic, Ali H. Mokdad, Lorenzo Monasta, Ghobad Moradi, Paula Moraga, Seyyed Meysam Mousavi, Ulrich Otto Mueller, Srinivas Murthy, Ghulam Mustafa, Aliya Naheed, Gurudatta Naik, Charles Richard James Newton, Yirga Legesse Nirayo, Molly R Nixon, Richard Ofori-Asenso, Felix Akpojene Ogbo, Andrew T Olagunju, Tinuke O Olagunju, Bolajoko Olubukunola Olusanya, Justin R Ortiz, Mayowa Ojo Owolabi, Shanti Patel, Gabriel D. Pinilla-Monsalve, Maarten J Postma, Mostafa Qorbani, Alireza Rafiei, Vafa Rahimi-Movaghar, Robert C Reiner, Andre M. N. Renzaho, Mohammad Sadegh Rezai, Kedir Teji Roba, Luca Ronfani, Gholamreza Roshandel, Ali Rostami, Hosein Safari, Saeed Safari, Saeid Safiri, Rajesh Sagar, Abdallah M. Samy, Milena M Santric Milicevic, Benn Sartorius, Shahabeddin Sarvi, Monika Sawhney, Sonia Saxena, Azadeh Shafieesabet, Masood Ali Shaikh, Mehdi Sharif, Mika Shigematsu, Si Si, Eirini Skiadaresi, Mari Smith, Ranjani Somayaji, Mu'awiyyah Babale Sufiyan, Nega Yimer Tawye, Mohamad-Hani Temsah, Miguel Tortajada-Girbés, Bach Xuan Tran, Khanh Bao Tran, Kingsley Nnanna Ukwaja, Irfan Ullah, Isidora S Vujcic, Fasil Shiferaw Wagnew, Yasir Waheed, Kidu Gidey Weldegwergs, Andrea Sylvia Winkler, Charles Shey Wiysonge, Alison B. Wiyeh, Grant M. A. Wyper, Ebrahim M. Yimer, Naohiro Yonemoto, Zoubida Zaidi, Zerihun Menlkalew Zenebe, Valery L. Feigin, Theo Vos, Christopher J L Murray
Gesehen am 30.04.2020